PENGARUH RISIKO LITIGASI TERHADAP KUALITAS PELAPORAN KEUANGAN DENGAN KEAHLIAN HUKUM KOMITE AUDIT SEBAGAI VARIABEL PEMODERASI (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia periode 2010-2012) - Asti Awalia; Daljono Daljono (Diponegoro Journal of Accounting, 2014)
The quality of financial reporting becomes an important basis for decision-making parties with an interest in the company. This study aims to obtain empirical evidence about the relationship between the financial reporting quality, litigation risks, and the audit committee of legal experts. Financial reporting quality measured using discretionary accruals value that indicates whether there is any indication of earnings management. The study used a sample of companies listed on the Indonesia Stock Exchange over the period 2010-2012 were obtained by purposive sampling method based on certain criteria. The total final samples used in this study were 61 companies. Technical analysis is the analysis of Moderated Regression Analysis. Statistical test results showed that the risk of litigation research significant positive effect on discretionary accruals, which is an inverse measure of the financial reporting quality. In addition, the results show no evidence that the legal experts audit committee moderating the relationship between litigation risk and the quality of financial reporting.